Pd-catalyzed isocyanide insertion/nucleophilic attack by indole C-3/desulfonylation in the same pot: a direct access to indoloquinolines of pharmacological interest1. Issue 77 (22nd August 2015) - Prasad, Bagineni; Nallapati, Suresh Babu; Kolli, Sunder Kumar; Sharma, Atul Kumar; Yellanki, Swapna; Medisetti, Raghavender; Kulkarni, Pushkar; Sripelly, S.; Mukkanti, K.; Pal, Manojit
<x xml:space="preserve">Abstract</x> A Pd-catalyzed new cascade reaction furnished indoloquinolin based small molecules as potential cytotoxic agents.